IDEAS OF THE JADIDS ON ENSURING PUBLIC WELFARE - Madaminov, Diyorbek (International Conference on Linguistics & Translation, 2026)
This article analyzes the ideas of the Jadid movement representatives concerning public welfare and social development. Jadid thinkers considered education, enlightenment, economic activity, and national consciousness as key factors for the progress of society. The article examines the ideas of Mahmudhoja Behbudi, Abdulla Avloni, Munavvarqori Abdurashidkhanov, and Abdurauf Fitrat and evaluates their relevance in modern educational and social reforms.